K.eyes: an application to assist in the self-makeup process for visually impaired women - Pereira, Rute Cristina da Silva; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Visual impairment is a condition that is very present in society and that has been growing due to a series of factors. This condition can affect self-esteem when some processes are limited to visual aspects. Make-up, widely used for correction, enhancement and beautification, is a practice that is very present in people’s lives, however, it still has some barriers to use for those with visual impairments, and need to be offered proposals that facilitate the use of products by people with this condition, in order to include them in this branch, as it ensures accessibility. The prototype presented here, entitled “K.eyes”, seeks to provide visually impaired women with technological support capable of communicating with them during the self-makeup process, based on data that would be obtained with computer vision. For requirements gathering, a study was carried out from the analysis of an accessible online channel, interviews with the target audience were done and an exploratory research was done on a self-makeup teaching channel for a visually impaired person. As a result, a prototype developed in a mobile version is presented, which was evaluated through a usability test with 6 blind or low vision women. The analysis of the results shows that the application is of great interest to women with visual impairments and has great potential to help in the self-makeup process.